Identifying key predictors amongst children of under 5 years of age with fever and rashes amidst measles outbreak in Jharkhand: A case control study - Dewesh Kumar; Vidya Sagar; Anit Kujur; Sanjay Bhardwaj; Vanesh Mathur; Rahul Kapse; Kaninika Mitra; Rishabh Kumar Rana; Rajan Kumar Barnwal; Bijit Biswas; Syed Irfan Ali; Ravi Ranjan Jha; et al. (PLoS ONE, 2025)
Background There has been a recent rise of viral exanthem outbreaks in Jharkhand and other parts of India over the last 2–3 years. This may be due to low immunization coverage of measles vaccination or due to spread of other causes of fever and rash. This study aims to identify the key predictors of fever and rashes among children under five years old by analysing demographic, clinical, and environmental factors. Methods This study employed age-matched case-control design to investigate the association between fever with rash (cases) and the absence of such symptoms (controls), along with identifying potential predictors. The study was conducted retrospectively among children aged 0–60 months who presented with fever and rash at various healthcare centres across affected districts in Jharkhand during a measles outbreak from January to May 2023. We included 611 cases and control thus making total sample size to be 1222. Multivariable logistic regression was performed to identify independent risk factors associated with fever and rash during the outbreak. Results The mean age for cases was found to be 37.37 ± 22.8 months and while for control it was found to be 25.89 ± 18.6 months. Majority of cases with fever with rash were found among the female child, 50.6% (279) but was not statistically significant. Significant factor as fever and rashes were found to be more amongst the children 200 (68.5%) who had not taken first dose and 325 (53%) of cases who had not taken second dose of measles vaccine with P-value of less than 0.001 and 0.022 respectively. On applying Multivariate analysis religion was 2.5 times more associated and even ethnicity was 3 times more associated with the fever and rash cases. Conclusion The study concludes that ethnicity, religion, and caste are important predictors of fever and rash cases. The most important factor is non-receipt of all age-appropriate vaccine as one of key factors for fever and rashes. The sociodemographic factors have a crucial role in transmission of viral exanthem and stakeholders must keep a vigil over these factors while dealing outbreaks of fever with rash disease.